Analisis Pengarusutamaan Gender di Indonesia, 2000-2023: Pendekatan Institusionalisasi - Nurdin, Nurdin (LPPM Institut Pendidikan Nusantara Global, 2024)
The institutionalization of gender mainstreaming is an important and decisive step in encouraging successful implementation at both the Central and Regional Levels in Indonesia. After almost two decades (2000-2023) the establishment of gender mainstreaming policies in Indonesia still faces institutionalization obstacles. These institutional barriers are an important factor in the stagnation of implementing gender mainstreaming in Indonesia. The research method used was a qualitative approach related to gender mainstreaming policy issues in Indonesia. Data collection was carried out through literature studies of official documents, online news, books and previous research articles using an institutionalization approach. The research results explain that the stagnation of gender mainstreaming policies in Indonesia, both in Ministries/State Institutions and Regional Governments, is due to weak institutionalization efforts by the government and regional governments which has an impact on the slow integration of gender analysis into gender planning and budgeting.